“It should just be about sport!”: exploring Italian athletes' perspectives in paralympic media coverage - Athanasios (Sakis) Pappous; Pablo Gómez-Iniesta (Frontiers in Sports and Active Living)
This study explores how Italian Paralympic athletes perceive their representation in the media, shifting the analytical focus from media texts to the lived experiences of the athletes themselves across their sporting careers. Using semi-structured interviews and a hybrid inductive–deductive thematic analysis, the research identifies key themes in how athletes evaluate current media coverage. Findings reveal that while visibility has improved, narratives remain dominated by stereotypical frames—such as the “supercrip” or pity narratives—that marginalise athletic performance. Athletes advocate for more balanced, sport-centered coverage and highlight the role of self-representation through social media in challenging mainstream portrayals. Drawing on theories of framing, representation, and disability models, the study underscores the importance of incorporating athletes’ voices to advance inclusive and accurate media narratives.